Strategi Frugal Living Dalam Pendidikan Islam Nonformal Untuk Penguatan Nilai Zuhud Dan Qanaah - Elysa Nurul Qomaria (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This research analyzes the application of frugal living as a strategy to strengthen Islamic values, particularly zuhd (asceticism) and qana'ah (contentment), among young mothers through non-formal Islamic education in Plosokerep Village, Sumobito, Jombang. As consumerism increases, even in rural areas, it is important to equip people with values that promote simple living rooted in Islamic teachings. This descriptive qualitative research used interview methods, participatory observation, and documentation of educational activities at the local Muslimah recitation group. The findings show that when frugal living is framed with Islamic principles, the participants experience increased awareness of the importance of contentment, wise financial management, and inner peace. This research contributes to the development of community-based Islamic education as an effective means to internalize spiritual values in daily life. The conclusion emphasizes that frugal living is not just an economic lifestyle, but a contextual tool to build spiritual character.